Altered Cervical Mucosal Gene Expression and Lower Interleukin 15 Levels in Women With Schistosoma haematobium Infection but Not in Women With Schistosoma mansoni Infection. (25th December 2018) - Dupnik, Kathryn M; Lee, Myung Hee; Mishra, Pallavi; Reust, Mary Juliet; Colombe, Soledad; Haider, Syeda Razia; Yao, Benjamin; Vick, Kaitlin; Zhang, Tuo; Xiang, Jenny; Miyaye, Donald; Magawa, Ruth; et al.
Abstract: Background: Schistosomiasis increases the risk of human immunodeficiency virus (HIV) acquisition in women by mechanisms that are incompletely defined. Our objective was to determine how the cervical environment is impacted by Schistosoma haematobium or Schistosoma mansoni infection by quantifying gene expression in the cervical mucosa and cytokine levels in cervicovaginal lavage fluid. Methods: We recruited women with and those without S. haematobium infection and women with and those without S. mansoni infection from separate villages in rural Tanzania with high prevalences of S. haematobium and S. mansoni, respectively. Infection status was determined by urine and stool microscopy and testing for serum circulating anodic antigen. RNA was extracted from cervical cytobrush samples for transcriptome analysis. Cytokine levels were measured by magnetic bead immunoassay. Results: In the village where S. haematobium was prevalent, 110 genes were differentially expressed in the cervical mucosa of 18 women with versus 39 without S. haematobium infection. Among the 27 cytokines analyzed in cervicovaginal lavage fluid from women in this village, the level of interleukin 15 was lower in the S. haematobium –infected group (62.8 vs 102.9 pg/mL; adjusted P = .0013). Differences were not observed in the S. mansoni –prevalent villages between 11 women with and 29 without S. mansoni infection. Conclusions: We demonstrate altered cervical mucosal gene expression and lower interleukin 15 levels in women with S. haematobium infection as compared to those with S. mansoni infection, which may influence HIV acquisition and cancer risks. Studies to determine the effects of antischistosome treatment on these mucosal alterations are needed. Abstract : This case-control study found altered cervical mucosal gene expression and lower cervicovaginal interleukin 15 levels in women with Schistosoma haematobium infection but not in those with Schistosoma mansoni infection, which may influence human immunodeficiency virus acquisition and cancer risks.